2007
DOI: 10.2337/db06-0493
|View full text |Cite
|
Sign up to set email alerts
|

Altered Natural Killer Cells in Type 1 Diabetic Patients

Abstract: Evidence from animal models suggests that natural killer (NK) cells can be important players in the development of type 1 diabetes, although data in humans are still sparse. We studied the frequency and activation state of blood NK cells at different stages of human type 1 diabetes, and whether genetic or phenotypic NK cell peculiarities could be associated with an early onset of diabetes. The onset period is marked by a slight reduction in blood NK cells, but these are unusually activated in some patients (␥-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
134
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(155 citation statements)
references
References 48 publications
18
134
1
2
Order By: Relevance
“…Supporting this model was the elution of retinal autoantigens from HLA-A29 molecules. 55 Predominance of KIR2DS2, 2DS3 and 2DS4, the genes implicated in autoimmune diseases [56][57][58] in BCR patients compared to HLA-A*29-matched controls, suggests that these aKIR receptors may enhance the T-cell autoreactivity. Although the direct role of NK cells in BCR pathogenesis is not clear, the genetic data presented herein indicate that KIR-HLA combinations likely influence both CTL and NK cell responses toward tolerance in controls and autoimmunity in BCR patients ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting this model was the elution of retinal autoantigens from HLA-A29 molecules. 55 Predominance of KIR2DS2, 2DS3 and 2DS4, the genes implicated in autoimmune diseases [56][57][58] in BCR patients compared to HLA-A*29-matched controls, suggests that these aKIR receptors may enhance the T-cell autoreactivity. Although the direct role of NK cells in BCR pathogenesis is not clear, the genetic data presented herein indicate that KIR-HLA combinations likely influence both CTL and NK cell responses toward tolerance in controls and autoimmunity in BCR patients ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Relatively weaker inhibitory signals triggered by the predominant interactions of KIR2DL2/3 þ HLA-C1 and KIR3DL1 þ HLA-Bw4 T80 in patients may be sufficient to establish NK cell tolerance to self in the resting state, 27 but may be easily overcome by activating signals triggered in response to stress such as infection, leading to disease. The preponderance of autoimmunity- iKIR+HLA only iKIR+HLA+aKIR *** associated activating receptors KIR2DS2, 2DS3 and 2DS4 [56][57][58] in patients suggests that the interaction between these aKIRs and determinants expressed on the surface of stressed intraocular tissue trigger signals that may overcome the weaker inhibition, favoring localized NK cell hyperresponsiveness against self. Of note, individuals carrying the compound genotype (KIR2DL2/3 þ HLA-C1, KIR3DL1 þ HLA-Bw4 T80 and KIR2DS2/S3/S4) are extremely rare in black and Asian populations, 47 which is consistent with the epidemiology of BCR.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the lower cytotoxicity displayed by NOD NK cells are likely multifactorial, but previous studies of NK cells from human T1D patients show significantly lower cytotoxicity and decreased expression of activating receptors. 8,50 The observed cytotoxicity against CHO targets and the unusually large number of activating Ly49 in NOD mice, is especially intriguing in light of recent reported correlations between diabetes incidence and the number of activating KIR expressed by an individual's NK cells. 8,25 Supporting evidence for this hypothesis is found in the observation that disease incidence is reduced in NOD mice congenic for the B6 NKC, 11 which encompasses the B6 Ly49 region and contains only two functional activating Ly49 in contrast to the seven predicted for NOD.…”
Section: Nod Mousementioning
confidence: 99%
“…An early study demonstrated that diabetic patients have lower NK activity compared to healthy controls, 7 whereas a second group found that NK cells isolated from diabetic patients showed an activated phenotype compared to NK cells from healthy controls. 8 Several recent studies have reported abnormal NOD NK cell functions and may be indicative of a possible association between diabetes development and NK cell dysfunction. [9][10][11] Cytotoxicity of NK cells from NOD mice against NK-sensitive tumor cell targets is lower than the killing activity from NK cells of nondiabetic mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation